Student-Produced Films in Laboratory Courses as Learning Incentive and Exam Option - Liv-Irene Berglund; Kirsten Krause (Nordic Journal of STEM Education)
An increasingly digitalized society demands that both educators and students master the use of digital tools in all teaching and learning activities. In laboratory-based courses, the practical elements of teaching are difficult to digitalize without sacrificing the important hands-on experience, leaving the remaining components such as seminars, reports or exams as possibilities where the classical concepts can be supplemented or replaced by digital solutions. In this paper we report on the use of digital film production as an alternative option for written laboratory reports and a means to intensify the learning outcome from practical experiments. Films were produced by students of the Bachelor course “Green Biotechnology and Bioenergy” on selected parts of the course. Simple and budget-friendly measures were implemented to carry out the filming. The films replaced the laboratory reports for the respective experiments. A seminar served as an interactive platform for the students to present their films to their fellow students and exchange feedback before the films were assessed by evaluators as part of the examination. The pedagogical benefits of this teaching method and its suitability as an assessment form were later analyzed to shed light on the question if student-produced films are a promising way to impart digital expertise effectively while acquiring practical skills in an informative and creative manner. Beyond advocating student-produced films as a possible exam concept for practical courses, our article demonstrates that self-executed filming was able to provide a more creative, interactive, and thus more motivating teaching atmosphere with mutually advantageous learning experiences for all parties involved.